Novel neutralizing chicken IgY antibodies targeting 17 potent conserved peptides identified by SARS-CoV-2 proteome microarray, and future prospects - Li, Jin; Liang, Te; Hei, Ailian; Wang, Xiangbin; Li, Huijun; Yu, Xiaobo; Zhao, Rui; Gao, Peng; Fang, Cong; Zhou, Ji; Li, Maogang; He, Ellen; et al. (Frontiers in Immunology, 2022)
Introduction An approach toward novel neutralizing IgY polyclonal antibodies (N-IgY-pAb) against SARS-CoV-2 S-ECD was developed. Material and methods The novel N-IgY-pAb and its intranasal spray response against the wild type (“‘WH-Human 1”) SARS-CoV-2 virus, variants of Delta or Omicron were up to 98%. Unique virus peptides binding to N-IgY-pAb were screened by a SARS-CoV-2 proteome microarray. Results Seventeen mutation-free peptides with a Z-score > 3.0 were identified as potent targets from a total of 966 peptides. The new findings show that one is in the RBM domain (461LKPFERDISTEIYQA475 ), two are in the NTD domain (21RTQLPPAYTNSFTRG35, 291CALDPLSETKCTLKS305) four are in the C1/2-terminal (561PFQQFGRDIADTTDA575,571DTTDAVRDPQTLEIL585,581TLEILDITPCSFGGV595, 661ECDIPIGAGICASYQ675 ), three are in the S1/S2 border (741YICGDSTECSNLLLQ755, 811KPSKRSFIEDLLFNK825, 821LLFNKVTLADAGFIK835) one target is in HR2 (1161SPDVDLGDISGINAS1175) and one is in HR2-TM (1201QELGKYEQYIKWPWY1215). Moreover, five potential peptides were in the NSP domain: nsp3-55 (1361SNEKQEILGTVSWNL1375), nsp14-50 (614HHANEYRLYLDAYNM642, ORF10-3 (21MNSRNYIAQVDVVNFNLT38, ORF7a-1(1MKIILFLALITLATC15) and ORF7a-12 (1116TLCFTLKRKTE121). Discussion and conclusion We concluded that the N-IgY-pAb could effectively neutralize the SARS-CoV-2. The new findings of seventeen potent conserved peptides are extremely important for developing new vaccines and “cocktails” of neutralizing Abs for efficient treatments for patients infected with SARS-CoV-2.